Critical-stress of thin-walled cylinders in axial compression - Batdorf, S. B.; Schildcrout, Murry; Stein, Manuel (Technical note (United States. National Advisory Committee for Aeronautics), 1947)
Empirical design curves are presented for the critical stress of thin-walled cylinders loaded in axial compression. These curves are plotted in terms of nondimensional parameters of small-deflection theory and are compared with theoretical curves derived for the buckling of cylinders with simply supported and clamped edges. An empirical equation is given for the buckling of cylinders having a length-radius ratio greater than about 0.75. The test data obtained from various sources follow the general trend of the theoretical curve for cylinders with clamped edges, agreeing closely with the theory in the case of short cylinders, but falling considerably below the theoretical results for long cylinders. --